Dispute resolution management relating to Waqf: a learning lesson from tanah Wakaf Abdul Cauder, Pulau Pinang - Mohd. Zain, Nor Razinah; Abdul Rahim, Rabiatul Adawiyah; Mohd Noor, Azman (2019)
Waqf is an Islamic philanthropy instrument created by the Waqif for the sake of Allah Almighty. It celebrates the elements of perpetuality and charitability. The emergence of disputes relating to Waqf may disturb its potentials to be utilized at its full capacity. This research analyses the dispute resolution management relating to Waqf, with a specific study relating to Tanah Wakaf Abdul Cauder, Pulau Pinang. Depending on the qualitative research methodology, this research uses the library-based research and secondary database in the construction of evaluation and findings. In resolving and managing dispute involving Waqf, it is pertinent to consider the existing laws and relevant jurisdictions. All the relevant stakeholders must cooperate to reach a proper dispute resolution and ultimately uphold the position of Shariah as high as it should be. Moreover, awareness and understanding of the stakeholders concerning to Waqf are needed to appreciate the rights relating to it. This research is done to contribute a pragmatic consideration on the dispute resolution management relating to Waqf in Malaysia. For the sake of sustainability of Waqf institutions in Malaysia, it is important to consider the dispute resolution management. This is necessary to protect the rights of relevant stakeholders and beneficiaries.